The Effectiveness of a Differentiated Learning Approach: Creativity and Elementary School Students' IPAS Learning Outcomes - Asmaul Husna Kasim; Supriadi Supriadi; Erwin Nurdiansyah (Education and Talent Development Center Indonesia (ETDC Indonesia), 2026)
This research is motivated by the low level of creativity and student learning outcomes in Natural and Social Sciences (IPAS) subjects in grade V at Elementary School Lantebung, Makassar City, which is caused by conventional learning processes that have not accommodated the diversity of student characteristics. The purpose of this study is to test the effectiveness of the implementation of a differentiated learning approach in improving students' creativity and learning outcomes in IPAS. The research method used is a quasi-experimental design with the one-group pretest-posttest design on 37 grade V students. Data collection techniques were carried out through learning outcome tests, observations of teacher and student activities, and creativity assessments. Data was analyzed using descriptive statistics and paired sample t-tests. The results showed a significant transformation in the classroom ecosystem, marked by a progressive increase in teacher pedagogical competence (64% to 93%) and student learning activities (60% to 89%). Academically, the average value of learning outcomes increased sharply from 47.43 to 76.89 (t = 18.073; p < 0.000), with a drastic decrease in standard deviation from 11.99 to 6.38, proving a reduced understanding gap among students. Furthermore, this strategy significantly stimulated all aspects of divergent thinking (t = 26.760; p < 0.000), with optimal development in flexibility and elaboration. In conclusion, differentiated learning is an empirically valid, effective, and inclusive model that is highly adaptive to students' characteristics, interests, and learning readiness in maximizing both cognitive potential and creativity in elementary schools.